(Bio)dissolution of arsenopyrite coupled with multiple proportions of pyrite: Emphasis on the mobilization and existential state of arsenic. (April 2023) - Tang, Anni; Wang, Jun; Zhang, Yisheng; Hong, Maoxin; Liu, Yang; Yang, Baojun
Abstract: The formation of arsenic-bearing acid mine drainage (AMD) via the oxidation of arsenopyrite refuse ore has attracted significant attention. Pyrite, as main a concomitant mineral, is a crucial factor that affects the (bio)dissolution of arsenopyrite, but there are still some points on the detailed action mechanism under normal environmental conditions that need further study. In this study, the effect mechanism of pyrite with a systematic pyrite content (0, 10, 25, 50, 75, 90, and 100 wt %) on arsenopyrite oxidation and arsenic release in the presence of Acidithiobacillus ferrooxidans was investigated. The X-ray diffraction (XRD), scanning election microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and electrochemical analyses were also carried out. Results showed that the existence of pyrite and Acidithiobacillus ferrooxidans significantly accelerated the dissolution of arsenopyrite and the oxidation of As (Ⅲ) to As (Ⅴ), resulting from the galvanic effect, an increase in the Fe 3+ /Fe 2+ ratio and the oxidation–reduction potential (Eh) value, and a decrease in pH level. As the detected main intermediate products, element sulphur was considered as the dominating obstructive factor during arsenopyrite oxidation, while the added pyrite could accelerate its oxidation. Moreover, a close relationship between different mineral proportions and the galvanic effect was also observed and discussed. Finally, suggestions on AMD governance and source control are proposed. Graphical abstract: Image 1 Highlights: (Bio)dissolution of pyrite/arsenopyrite in an AMD-like environment is revealed. A systematic arsenopyrite/pyrite ratio (0, 10, 25, 50, 75, 90, 100 wt%) is used. The effect of different mineral proportions on galvanic effect is proposed. The oxidation of As (III) to As (V) with lower toxicity is facilitated by pyrite. Some suggestions on AMD governance and source control are put forward.